A Randomized Comparative Effectiveness Trial of Two Court‐Connected Programs for High‐Conflict Families. (6th July 2016) - Braver, Sanford L.; Sandler, Irwin N.; Cohen Hita, Liza; Wheeler, Lorey A.
Abstract : Parents who experience great amounts of legal conflict as they dissolve their relationship and arrive at their parenting arrangements require an outsize proportion of courts' time and resources. Additionally, there is overwhelming evidence that conflict has a deleterious effect on their children. We partnered with the family court to conduct a study comparing the effectiveness of two programs for families deemed by their judge to be high conflict and thereby mandated to a program. Both involved one 3‐hour session; the existing program, Parent Conflict Resolution (PCR), used exhortational lecture and video; the newly designed experimental program, Family Transitions Guide (FTG), based on motivational interviewing, employed exercises attempting to get parents to decide for themselves what they needed to do for the sake of their children. Parents were assigned at random to one of the two programs (the literature often terms this a randomized clinical trial) and were interviewed just before it began and 9 months later, as was a child. Results showed that child's report of their own well‐being was significantly improved by FTG as compared to PCR and that these effects were mediated by children feeling less caught in the middle. On several variables, parent report showed that parents in PCR as compared to FTG felt decreased problems in co‐parenting and less interparental conflict, although the effects were not consistent across mother and father report. There was also evidence of diminished legal conflict over 9 months in FTG as compared to PCR. Key Points for the Family Court Community: Legal conflict is a great problem for courts and interparental conflict a distinct problem for divorcing families. We developed a program for high‐conflict families, Family Transitions Guide (FTG), derived from a motivational interviewing approach. FTG was compared to the usual such program, Parent Conflict Resolution (PCR), in a randomized trial. Children's report of their own well‐being was significantly improved by FTG as compared to PCR, due to children feeling less caught in the middle. There was also evidence of diminished legal conflict over 9 months in FTG as compared to PCR.